DETERMINANT OF NGM’S INTENTION TO CONTINUE THE FAMILY BUSINESS - Heaviside, Marceline; Nuringsih, Kartika (Graduate Program of Universitas Tarumanagara, 2024)
Family businesses encounter succession crisis, with only 10% to 15% successfully transitioning to the third generation. The sustained operation and growth of family enterprises are intricately linked to the effectiveness of generational transitions. The absence of a structured transition process in family business continuity often stems from the insufficient interest and commitment of the Next Generation Members (NGM) to perpetuate their family enterprises. Hence, there is a pressing need for research into the determinants influencing NGM's intentions to sustain family businesses. This study investigates and evaluates the impacts of career interest, self-efficacy, and parental support on NGM's intentions to continue family businesses. Employing a non-probability sampling technique, data is collected through an online Google Form questionnaire from 121 respondents. Data analysis is conducted using SmartPLS. The study sample comprises NGMs based in Jakarta. The findings revealed that career interest positively and significantly shaped NGM's intentions to continue family businesses, self-efficacy similarly exerts a positive and significant impact, while parental support yields a negative and non-significant effect on NGM's intentions to continue family businesses. The results of this study provide information for family business owners in preparing for business succession in the future.